NLRP3 inflammasome in cardiovascular diseases: an update - Mo, Binhai; Ding, Yudi; Ji, Qingwei (Frontiers in Immunology, 2025)
Cardiovascular disease (CVD) continues to be the leading cause of mortality worldwide. The nucleotide oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome is involved in numerous types of CVD. As part of innate immunity, the NLRP3 inflammasome plays a vital role, requiring priming and activation signals to trigger inflammation. The NLRP3 inflammasome leads both to the release of IL-1 family cytokines and to a distinct form of programmed cell death called pyroptosis. Inflammation related to CVD has been extensively investigated in relation to the NLRP3 inflammasome. In this review, we describe the pathways triggering NLRP3 priming and activation and discuss its pathogenic effects on CVD. This study also provides an overview of potential therapeutic approaches targeting the NLRP3 inflammasome.